Effect of methane presence on catalytic heavy oil partial upgrading. (1st August 2021) - Li, Zhaofei; Li, Yimeng; Xu, Hao; Jarvis, Jack; Meng, Shijun; Song, Hua
Highlights: Methanotreating technique can be applied into a wide range of heavy oil. Methane presence promotes heavy ends conversion. Methane presence effectively suppresses thermal over-cracking. Methane might be incorporated into the liquid product. Methane presence facilitates deoxygenation and desulfurization reactions. Abstract: In this work, several heavy crudes with wide viscosity range from 1200 to 120, 000 cP at 15.6 °C were partially upgraded with a specially designed catalyst under CH4 atmosphere. All these reactions were conducted using a batch mode high temperature and high-pressure Parr reactor. This technique was proved to be suitable for the heavy oil feeds with varied properties, confirming its generality for industrial practice. Upgrading under CH4 demonstrated much better performance than that under N2 when the reaction conditions kept the same, confirming the role played by methane on facilitating heavy ends conversion during heavy oil partial upgrading. Furthermore, the effect of methane presence was further investigated through comparing with its N2 counterpart at the similar asphaltene conversion by tuning the reaction time and temperature. Although it is well expected that coke yield and gas yield increased yet liquid yield decreased along with upgrading reaction proceeding, the reaction under CH4 showed noticeably lower coke and gas yield while higher liquid yield than its counterpart under N2 at comparable asphaltene conversion, strongly indicating the methane's effect on effective suppression of thermal over-cracking of heavy crude, which is beneficial for achieving more high value-added liquid products. Moreover, the properties of the oil products derived from different atmospheres including viscosity, density, TAN (total acidic number), AMW (average molecular weight) and sulfur content were studied and compared. All these indexes showed a decreasing trend with increasing asphaltene conversion. The values for viscosity, density and AMW were higher under CH4 than those under N2, while the TAN and sulfur content were lower when methane was present, implying the possible methane incorporation and its role played on promoting deoxygenation and desulfurization reactions. The research outcomes derived from this study further evidence the technical advantages of heavy crude partial upgrading under methane, thus providing a more cost-effective and environmentally friendly alternative to hydrotreating for processing heavy oil.